2020
DOI: 10.3390/ijms21217821
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Mass Spectrometry for In Vivo Proteome Dynamics using Heavy Water Metabolic Labeling

Abstract: Cellular proteins are continuously degraded and synthesized. The turnover of proteins is essential to many cellular functions. Combined with metabolic labeling using stable isotopes, LC–MS estimates proteome dynamics in high-throughput and on a large scale. Modern mass spectrometers allow a range of instrumental settings to optimize experimental output for specific research goals. One such setting which affects the results for dynamic proteome studies is the mass resolution. The resolution is vital for disting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…With knowledge of the initial predicted precursor labelling (based on body water levels), and the peptide amino acid composition i.e. knowledge of the number of each theoretically labelled AA, rates of turnover of individual peptides and hence the parent proteins, can be calculated [77,79]. This has been extensively validated in animal and cell culture models [80e82] and more recently in humans too [71,78,83].…”
Section: Referencementioning
confidence: 99%
“…With knowledge of the initial predicted precursor labelling (based on body water levels), and the peptide amino acid composition i.e. knowledge of the number of each theoretically labelled AA, rates of turnover of individual peptides and hence the parent proteins, can be calculated [77,79]. This has been extensively validated in animal and cell culture models [80e82] and more recently in humans too [71,78,83].…”
Section: Referencementioning
confidence: 99%
“…We therefore employed a high-resolution tribrid mass spectrometer using HCD and ETD fragmentation methods to investigate changes in the proteome of the left ventricle of the heart, including the identification of 4-HNE–modified proteins, of control and exercised mice. According to the study published several months ago, it is possible that lowering the value for the mass resolution of the mass spectrometer would lead to better protein identification ( Sadygov, 2020 ). In addition, proteins with modifications that were not specified in the database search may result in the lack of protein identification.…”
Section: Discussionmentioning
confidence: 99%
“…For the Orbitrap instrument, it is not preferable to use too high a mass resolution. It was observed that 60,000 is the best choice for the balance between resolving interference peaks and spectral accuracy (Naylor et al, 2017; Sadygov, 2020a). Zoom scan or target‐SIM mode (e.g.…”
Section: Protein Turnover Rate Calculation For Metabolic Study With 2...mentioning
confidence: 99%